A SOX17-PDGFB signaling axis regulates aortic root development - Pengfei Lu; Ping Wang; Bingruo Wu; Yidong Wang; Yang Liu; Wei Cheng; Xuhui Feng; Xinchun Yuan; Miriam M. Atteya; Haleigh Ferro; Yukiko Sugi; Grant Rydquist; et al. (Nature Communications, 2022)
Little is known about the developmental causes of aortic root defects. Here the authors show that the inactivation of Sox17 in aortic root endothelium results in aortic root defects affecting aortic valve and coronary ostium.